Business stealing + economic rent = insufficient entry? An integrative framework - Marco De Pinto; Laszlo Goerke; Alberto Palermo (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2024)
Entry in a homogeneous Cournot oligopoly can be excessive if there is business stealing. Since this excessive entry prediction has been established, a variety of circumstances have been identified which allow for insufficient entry, despite the business stealing externality. This paper shows that most of them rely on the same mechanism and, therefore, constitute a special case of a general set-up. To establish this insight, we survey the pertinent contributions and classify the circumstances, which are invoked to establish the possibility of insufficient entry into four categories. Importantly, they all imply that the oligopolists pay a rent, which reduces profits and deters entry. Since rents are welfare-neutral, insufficient entry will occur if the rent is high enough.
Keywords: D43; D62; L13; 330; Business stealing; Cournot oligopoly; Economic rent; Excessive entry; Insufficient entry; Literature survey